2021
DOI: 10.1111/wrr.12977
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of LL‐37 in healing of hard‐to‐heal venous leg ulcers: A multicentric prospective randomized placebo‐controlled clinical trial

Abstract: Many patients with venous leg ulcers do not reach complete healing with compression treatment alone, which is current standard care. This clinical trial HEAL LL-37 was a phase IIb double-blind, randomized, placebo-controlled study, with the aim to evaluate the efficacy and safety of a new drug LL-37 for topical administration, in combination with compression therapy, in 148 patients suffering from hard-to-heal venous leg ulcers. The study had three arms, consisting of two groups treated with LL-37 at concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…Lactate dehydrogenase (LDH) release assays showed that As-CATH8 and Gg-CATH5 were moderately cytotoxic against human bronchial epithelial (HBE) cells and peripheral blood mononuclear cells (PBMCs) ( Supplementary Figure S3 ), at the highest concentrations tested (5 and 10 μM). This effect was similar to that observed for the natural human cathelicidin LL-37, which has been used in a phase 1 human clinical trial [ 31 ]. In contrast, the crocodylian peptides As-CATH7 and Gg-CATH7 showed low cytotoxicity against both cell types, comparable to the immunomodulatory peptide IDR-1018 used as control.…”
Section: Resultssupporting
confidence: 79%
“…Lactate dehydrogenase (LDH) release assays showed that As-CATH8 and Gg-CATH5 were moderately cytotoxic against human bronchial epithelial (HBE) cells and peripheral blood mononuclear cells (PBMCs) ( Supplementary Figure S3 ), at the highest concentrations tested (5 and 10 μM). This effect was similar to that observed for the natural human cathelicidin LL-37, which has been used in a phase 1 human clinical trial [ 31 ]. In contrast, the crocodylian peptides As-CATH7 and Gg-CATH7 showed low cytotoxicity against both cell types, comparable to the immunomodulatory peptide IDR-1018 used as control.…”
Section: Resultssupporting
confidence: 79%
“…In the context of UTI, AMPs such as defensins [ 8 ], the ribonuclease A superfamily [ 9 ] and LL-37, the only member of the cathelicidin family found in humans [ 10 ], are part of the innate immunity protecting the host from invading pathogens. Currently, synthetic LL-37 is being used in clinical trials treating venous leg ulcers [ 11 , 12 ]. Despite the interesting bioactivities of LL-37, its direct utility in a clinical setting has been hampered due to its toxicity to human cells and proteolytic instability [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…An earlier randomized, placebo-controlled trial demonstrated that the topical application of LL-37 can enhance the healing rate of chronic venous leg ulcers [ 139 ]. However, that was not corroborated in a newer trial, and it was still concluded that this human synthetic peptide could offer a certain treatment benefit in individuals with large ulcers [ 140 ]. Although the exact mechanism of wound repair is still elusive, there is a supposed effect of LL-37 in modulating the inflammatory response and driving angiogenesis together with re-epithelialization [ 125 , 141 ].…”
Section: Clinical Application Of Ampsmentioning
confidence: 99%